An investigation into fourth-year students’ instructions in speaking lessons in their teaching practicum at english division i, faculty of english language teacher education, University of Languages and International Studies-Vietnam National University, Hanoi = Nghiên cứu về lời hướng dẫn của giáo sinh thực tập trong giờ dạy nói cho sinh viên năm thứ nhất tại khoa tiếng anh, trường Đại học Ngoại ngữ, Đại học Quốc gia Hà Nội - Hoàng, Linh Chi (2020)
This paper aims at investigating into the major problems that trainee teachers often encounter when delivering instructions for a speaking activity. By identifying these problems the researcher desires to figure out ways for these trainee teachers in particular and future teachers in general to improve their skill of giving and checking instructions. In other words, the objective of this study is to answer the two following research questions: 1. What are the problems trainee teachers often encounter when giving and checking instructions in speaking lessons? 2. What are the suggestions for better classroom instructions proposed by the supervisor?